PROVIDING HEAT ENERGY TO GREENHOUSES USING SOLAR AIR HEATER COLLECTORS - Boynazarov Bekzod Bakhtiyorovich; Uzbekov Mirsoli Odiljonovich (Zeta Repository, 2023)
In this article, the issue of providing heat energy to greenhouses using solar air-heater collectors in the climatic conditions of Uzbekistan was considered. For a greenhouse with a total area of 400 m2, a total of 20 rhombus-shaped solar air heater collectors accelerating heat processes, each with a working surface of 1 m2, are installed. Economic analysis of heat energy obtained from solar air heater collectors.